Hidroacanthoma simplex: dermoscopy and cryosurgery treatment - Karina Colossi Furlan; Priscila Kakizaki; Juliana Cabral Nunes Chartuni; José Alexandre Sittart; Neusa Yuriko Sakai Valente (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Hidroacanthoma simplex is a rare intraepidermal neoplasia that arises from the acrosyringial portion of the eccrine duct. Malignant transformation of hidroacanthoma simplex is reported in the literature and the treatment is performed with wide excision or Mohs micrographic surgery. We report the first case successfully treated with cryosurgery with a long-term follow up.